The Making of Good Supervision : Learning to Say "No" - Elliott, Jennifer (IMF Staff Position Notes; Staff Position Note, 2010)
The quality of financial sector supervision has emerged as a key issue from the financial crisis. While most countries operated broadly under the same regulatory standards, differences emerged in supervisory approaches. The international response to this crisis has focused on the need for more and better regulations (e.g., in areas such as bank capital, liquidity and provisioning) and on developing a framework to address systemic risks, but there has been less discussion of how supervision itself could be strengthened. The IMF's work in assessing compliance with financial sector standards over the past decade in member countries suggests that while progress is being made in putting regulation in place, work remains to be done in many countries to strengthen supervision. How can this enhanced supervision be achieved? Based on an examination of lessons from the crisis and the findings of these assessments of countries' compliance with financial standards, the paper identifies the following key elements of good supervision-that it is intrusive, skeptical, proactive, comprehensive, adaptive, and conclusive. To achieve these elements, the 'ability' to supervise, which requires appropriate resources, authority, organization and constructive working relationships with other agencies must be complemented by the 'will' to act. Supervisors must be willing and empowered to take timely and effective action, to intrude on decision-making, to question common wisdom, and to take unpopular decisions. Developing this 'will to act' is a more difficult task and requires that supervisors have a clear and unambiguous mandate, operational independence coupled with accountability, skilled staff, and a relationship with industry that avoids 'regulatory capture.' These essential elements of good supervision need to be given as much attention as the regulatory reforms that are being contemplated at both national and international levels. Indeed, only if supervision is strengthened can we hope to effectively deliver on the challenging-but crucial-regulatory reform agenda. For this to happen, society must stand with supervisors as they play their role as naysayers in times of exuberance.